Financial-sector foreign direct investment and host countries: New and old lessons - Linda Goldberg (Federal Reserve Bank of New York, 2004)
Many of the lessons from foreign direct investment (FDI) research on manufacturing and extractive resource industries are applicable to FDI research on the financial sector. This paper summarizes the main findings and policy themes of FDI research, with a primary focus on the implications of FDI for host countries, especially emerging market economies. I review evidence of technology transfers, productivity spillovers, wage effects, macroeconomic growth, and fiscal and tax concerns. Throughout this paper, I stress that parallel findings often arise from studies of general FDI and studies of financial-sector FDI. I also emphasize important differences between the effects of FDI in these sectors, especially with regard to local institution building and business cycles. These differences - more so than the similarities - should be the focus of research efforts.
Keywords: F3; F4; 330; Direktinvestition; Finanzsektor; Kritik